2005
DOI: 10.1111/j.1600-0765.2005.00815.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton and surface structures of cells directly attached to the tooth in the rat junctional epithelium

Abstract: DAT cells possess stress fibers arranged in parallel to the tooth axis and to the presumable cervical-line in the cytoplasm, and microvilli-like structures on their enamel surfaces. These results suggest that these structures contribute to DAT cell migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The cells directly attached to the tooth are well known to have the potential to migrate toward the crown side and adhere. However, the source of these cells is unclear, and determining whether the JE is replaced by the oral epithelium is difficult3839. To clarify whether the JE is maintained as the odontogenic epithelium or replaced by the oral epithelium, the re-formation of the JE following gingivectomy has been studied2540414243.…”
Section: Discussionmentioning
confidence: 99%
“…The cells directly attached to the tooth are well known to have the potential to migrate toward the crown side and adhere. However, the source of these cells is unclear, and determining whether the JE is replaced by the oral epithelium is difficult3839. To clarify whether the JE is maintained as the odontogenic epithelium or replaced by the oral epithelium, the re-formation of the JE following gingivectomy has been studied2540414243.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that lipopolysaccharide induces the apoptosis of periodontal ligament cells and the proliferation of basal cells in junctional epithelium . In addition, DAT cells migrate whilst attached to the enamel, and integrin α3β1 is involved in this migration . Furthermore, expression of keratinocyte growth factor receptor and hepatocyte growth factor receptor were reported to be up‐regulated in a rat model of periodontitis .…”
mentioning
confidence: 99%
“…Several investigators have proposed that DAT cells may be nonmigratory cells and that they do not participate in the turnover of the junctional epithelium (3,14,15). In contrast, other studies have reported evidence supporting a high turnover of DAT cells (16)(17)(18)(19). Thus, questions remain about whether DAT cells migrate to participate in cell turnover of the junctional epithelium (regardless of their expression of adhesion proteins), why there is no laminin (other than laminin-5) expressed in the internal basal lamina and how adhesion proteins are related to turnover of the junctional epithelium.…”
mentioning
confidence: 99%